2016
DOI: 10.1016/j.corsci.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Silane/TiO2 coating to control the corrosion rate of magnesium alloys in simulated body fluid

Abstract:  A well-developed silane/TiO 2 coating controlled corrosion rate of two Mg alloys.  The protective ability of the coating depends upon the nature of the alloy.  A Mg(OH) 2 and Ca/PO 4 containing layer of corrosion products was found.  The coating favors the formation of a non-stoichiometric hydroxyapatiterich layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 38 publications
1
48
0
Order By: Relevance
“…To overcome the challenges related to the use of Mg alloys, many studies have been working on finding ways to slow down the degradation of Mg alloys under physiological conditions in vitro through diverse approaches, such as development of new Mg alloys with different elements and deposition of anticorrosive coatings on Mg alloys substrates. Córdoba used a silane/TiO 2 coating to control the corrosion rate of Mg alloys in simulated body fluid [15]. Sachiko Hiromoto studied the self-healing properties of hydroxyapatite and octacalcium phosphate coatings on pure Mg and a Mg alloy [16].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the challenges related to the use of Mg alloys, many studies have been working on finding ways to slow down the degradation of Mg alloys under physiological conditions in vitro through diverse approaches, such as development of new Mg alloys with different elements and deposition of anticorrosive coatings on Mg alloys substrates. Córdoba used a silane/TiO 2 coating to control the corrosion rate of Mg alloys in simulated body fluid [15]. Sachiko Hiromoto studied the self-healing properties of hydroxyapatite and octacalcium phosphate coatings on pure Mg and a Mg alloy [16].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the study by Gaur et al showed a reduction of 3 orders of magnitude in low frequency impedance after nearly 12 days of immersion in SBF. Similarly, the study by Córdoba et al showed a reduction in low frequency impedance by half an order of magnitude in a silane‐TiO 2 composite after 14 days, but did not discuss the mechanism. When comparing studies, there is also a clear discrepancy between the methods used to quantify corrosion activity—studies tend to use hydrogen evolution, corrosion current density, corrosion potential, hydrogen evolution volume and any number of modelled parameters from equivalent circuit modelling.…”
Section: Biocorrosionmentioning
confidence: 95%
“…If R f decreases and CPE f increases, suggesting that the coating barrier properties are gradually deteriorating. Interestingly, when the corrosion started, Q for CPE f (0.62 < n < 0.77) was slightly increased, implying that electrolyte uptake was ongoing and the coating barrier properties started to deteriorate [34].…”
Section: / 22mentioning
confidence: 97%